Bob Burns Contributing columnist (Cimarron, New Mexico Cimarron Legend, 1992)
Article on the history of the Cimarron News and Press and the historical happening of Cimarron and Colfax County.
Master List Item # 20
File location is in the New Mexico File Cabinets
Keywords: Carson, Kit; Maxwell, Lucian; Harp, Choctaw Atoka; Murray, Shorty; Maxwell land Grant Company; Cimarron News and Press; Newspaper; Controversy; Local History; Indians; Mountain men; Gold mines; Coal; Ranching; Timber; Railroad; Cimarron, New Mexico; Colfax County, New Mexico; Cimarron River Valley